2004
DOI: 10.1002/asna.200410245
|View full text |Cite
|
Sign up to set email alerts
|

A search for luminous Be stars

Abstract: Abstract. As Be stars are restricted to luminosity classes III-V, but early B-type stars are believed to evolve into supergiants, it is to be expected that the Be phenomenon disappears at some point in the evolution of a moderately massive star, before it reaches the supergiant phase. As a first stage in an attempt to determine the physical reasons of this cessation, a search of the literature has provided a number of candidates to be Be stars with luminosity classes Ib or II. Spectroscopy has been obtained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 41 publications
(72 reference statements)
5
42
0
Order By: Relevance
“…Quoted as belonging to NGC 6913 (Humphreys 1978), HD 229234 was classified as an O 9If star by Massey et al (1995) whilst Negueruela (2004) reported an O 9II classification and Morgan et al (1955) reported this star as O 9.5III. Previous investigations of Liu et al (1989) and Boeche et al (2004) proposed this star to be a binary system with an orbital period of 3.5105 days.…”
Section: Hd 229234mentioning
confidence: 99%
“…Quoted as belonging to NGC 6913 (Humphreys 1978), HD 229234 was classified as an O 9If star by Massey et al (1995) whilst Negueruela (2004) reported an O 9II classification and Morgan et al (1955) reported this star as O 9.5III. Previous investigations of Liu et al (1989) and Boeche et al (2004) proposed this star to be a binary system with an orbital period of 3.5105 days.…”
Section: Hd 229234mentioning
confidence: 99%
“…This is Full Tables 1 and 4 are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/595/A132 in contrast to early-type supergiants in which emission in the Balmer lines is a "passive" consequence of their extended atmosphere. Even when some classic Be stars are believed to survive as such in the bright giant phase (Negueruela 2004), this definition excludes the heterogeneous group of objects presenting the B[e] phenomenon, which likely manifests at different states of stellar evolution (Lamers et al 1998). Be stars have long been known as rapid rotators (Struve 1931) and, accordingly, these stars are assumed to create their circumstellar disk or envelope thanks mainly to this rapid rotation.…”
Section: Introductionmentioning
confidence: 99%
“…A first run was made in 2003 with the 1.5 m telescope of the Observatorio Astronómico Nacional (OAN) in Calar Alto, Almería, Spain. A sample of emission-line stars from the catalogs by Kohoutek & Wehmeyer (1999, 2003, 2004 and Robertson & Jordan (1989) was observed. The targets were selected on the base of spectral types determined considering their position in the reddening-free [m 1 ] − [c 1 ] photometric diagram (Moon 1986).…”
Section: The Setting Up Of the Faint Be-star Samplementioning
confidence: 99%
“…Their Be phenomenon could be thought of as favored by the rotational acceleration they acquire during the secondary contraction phase. According to Negueruela (2004) some of them could even be interacting binaries. This figure also shows the evolutionary tracks of rotating stars whose initial equatorial rotational velocities in the ZAMS are V ini /V c = 0.4 (Ekström et al 2012).…”
Section: The Apparent and True Hr Diagram Of The Programmentioning
confidence: 99%
See 1 more Smart Citation